A STUDY ON VARIATION OF SURFACE GRAVITY OF BOSONIC FIELD AND FERMIONIC FIELD OF SPINNING BLACK HOLES - Paswan, Rakesh; Kumari, Bharti; Kumari, Niharika; Singh, Ramesh Kumar; Mahto, Dipo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper discusses the variation of surface gravity of Bosonic and Fermionic Fields of spinning black holes with different spin parameters of these categories of black holes for co-rotation as well as counter rotation and concludes that theBosonic, Fermionic and Other fields of specific rotations follows the same character as well as nature.